Multimedia development life cycle method for script making in the film kultur - Yoan Hadi Kusuma Admaja; Anisya Sonita (Borobudur Informatics Review, 2022)
The technique of making scripts in cultural films is a written work that aims to explain how important scripts are in filmmaking, where the script is the foundation for the formation of the film itself, besides that the writer also provides an explanation of the procedures for writing film scripts, starting from the beginning of the story idea to the formation of a script that can be adopted into a film, here the writer raises the theme of culture which is interpreted as culture, and the culture that is adopted here is the Bengkulu culture which is in such a way that it is almost extinct or obsolete, not only Introducing the importance and procedures for writing scripts, the author also educates a film entitled culture for the entire community, especially the Bengkulu people, with the aim of rebuilding the spirit of preserving the diversity of Bengkulu cultures which are almost extinct and obsolete.